Acing Your Strategy: A Human Approach to Successful Business Planning. - Audio Learning Inc., ProDio; Cullingworth, Russell (linkedin.com, 2022)
Learn about strategic and operational planning and, just as importantly, find out how to get others to engage with and adopt your strategy.